The Effectiveness of KMS Filling Training on the Accuracy of Immunization Cadres in Interpreting Weighing Results at RSIA Sitti Khadidjah Gorontalo City - Andi Akifa Sudirman; Wiwi Susanti Piola; Sri Susanti Domili (Universitas Ibn Khaldun Bogor, 2023)
KMS is a card containing the child's normal growth curve based on the anthropometric index of body weight according to age. The role of cadres related to monitoring growth and development is very important. The purpose of this study was to determine the effectiveness of KMS filling training on the accuracy of immunization cadres in interpreting weighing results. Pre-Experimental Research Design with One-Group pre-posttest approach. Sampling by probability sampling of as many as 13 respondents. Data collection using questionnaires (Pre-test and Post-test) and tested using paired t-test. The results showed that the average knowledge before (pretest) was 66.92 and after (posttest) given training became 78.23 with p = value 0.001 For the average value of skills before training (pretest) was 57.38 while after training (posttest) 86.23 with p = value 0.000. It can be concluded that there is an effectiveness of KMS filling training, and there is an accuracy of immunization cadres in interpreting weighing results.